The Effect of Simvastatin on Glucose Homeostasis in Streptozotocin Induced Type 2 Diabetic Rats - Lulu Wang; Guanglan Duan; Yong Lu; Shuguang Pang; Xianping Huang; Qiang Jiang; Ningning Dang (Journal of Diabetes Research)
Objective. To investigate the effect of simvastatin on glucose homeostasis in streptozotocin induced type 2 diabetic rats. Methods. Forty male Wistar rats were randomly divided into four groups. Normal control rats were fed with standard diet, others were fed with high-fat diet. Diabetic rats were induced by a single intraperitoneal injection of STZ. The simvastatin intervention rats were fed with simvastatin during the experiment process, and the simvastatin treatment rats were fed with simvastatin after diabetes rats were induced. We measured body weight, fasting plasma glucose, cholesterol, high-density lipoprotein cholesterol, and triglyceride after an overnight fast. Results. The FPG was higher in diabetic rats when compared to normal control ones; the simvastatin intervention rats had a higher FPG compared to the diabetic rats and were more easily be induced to diabetes at the end of 4 weeks, FPG level of simvastatin treatment rats was increased compared with diabetic model rats after 12 weeks. Conclusion. These data indicate that simvastatin intervention rats may cause hyperglycemia by impairing the function of islet β cells and have an adverse effect on glucose homeostasis, especially on FPG level.